International Coffee Hour (ICH) - Thailand (poster) - Lancaster, Kaitlyn; International Student Support Programs
Formerly known as?iam?,Thailand officially changed its name over 60 years ago, which means ?he Land of Free?. Besides its rich culture and deep history dating back more than 7 centuries,Thailand? serene temples, spectacular natural and modern urban cities make it a great place to visit.